Exploration of social dimensions of sustainable behavior - Toye, Samson Abiodun; Uygur, Mehmet Recai; Peyravi, Bahman (Business: Theory and Practice, 2025)
As climate change and inequality spur interest in sustainable lifestyles, insufficient attention focuses on the social dimension encompassing equity and wellbeing-oriented conduct. Limited measurements capture facets like frugality, sufficiency, and altruism, obscuring motivational nuances. Addressing persistent gaps, this exploratory sequential mixed-methods research developed and validated a multidimensional scale assessing components of individual social sustainability behavior. The initial qualitative generation of 167 items from established surveys enabled breadth. An expert review panel then evaluated content validity quantitatively through statistical relevance ratings and qualitatively via open-ended feedback on gaps and terminology issues to refine facets. Analyses informed iterative adjustments, resulting in a 45-item pool demonstrating sound psychometric properties. Quantitative techniques found strong internal reliability (α >.80) and confirmed dimensionality in distributing items across volunteering, charitable giving, conscious consumption, lifestyle simplicity, equity promotion, and community building sub-scales. Confirmatory factor analysis met thresholds for acceptable model fit. Qualitative inputs crucially enhanced practical resonance and specificity. Findings provide initial evidence of a valid, generalizable measurement of the social sustainability domain, encompassing cooperative civic engagement, frugality, and lifestyle moderation behaviors on the individual level. The parsimonious instrument promises utility for research and community initiatives advancing this complementary sustainability facet. Practical implications and scholarly contributions are discussed.